Positive Psychology in Islamic Counseling Perspective; Analysis of The Trilogy of Life Dimensions - Alfin Siregar (Al-Fikru: Jurnal Ilmiah, 2022)
Positive Psychology in the last two decades is considered one of the most productive findings in modern psychology. Because compared to some of the previous approaches, positive psychology emphasises the positive emotional side of humans. Meanwhile, the last method discussed more pathological issues; stress, depression, and others by way of healing. In this paper, we will see the concept of positive psychology from an Islamic counselling perspective. Islamic counselling as an analysis is not intended to discredit positive psychology but to add and enrich scientific insights into Islamic counselling. The method used is library research, with deductive-inductive characteristics in the data analysis. The results of this study indicate that Islamic counselling puts forward the values ​​of religiosity and spirituality without leaving the practical side. The trilogy that forms the basis of the positive psychology concept is a pleasant life, an engaged life, and the meaningful life in line with the goals of Islamic counselling. It's just that deepening in Islamic counselling on the concept of true happiness is not only when individuals can solve their problems or become optimistic individuals but understand the purpose of creating humans as God's creatures.